Dental Visits and Predictors of Regular Attendance Among Female Schoolchildren in Dammam, Saudi Arabia - Alhareky M; Nazir MA (Dove Medical Press, 2021)
Muhanad Alhareky, Muhammad Ashraf Nazir Department of Preventive Dental Sciences, College of Dentistry, Imam Abdulrahman Bin Faisal University, Dammam, Saudi ArabiaCorrespondence: Muhammad Ashraf Nazir Tel +966 543569615Email manazir@iau.edu.saPurpose: Regular dental visits are important for the maintenance of optimal oral health and improved quality of life. The purpose of the study was to evaluate patterns of dental visits and factors associated with routine dental attendance among female schoolchildren in Dammam, Saudi Arabia.Patients and Methods: This cross-sectional study was performed on 449 female primary schoolchildren (6– 11 years old) in Dammam, Saudi Arabia. The study included clinical examination for decay in the first permanent molars in children and questionnaire administration among their parents. The World Health Organization’s oral health questionnaire was used to collect data about children’s dental visits, oral hygiene behaviors, dental problems, and dietary practices. Bivariate and multivariate analyses were performed to evaluate factors associated with routine dental visits.Results: Most children (64.1%) visited the dentist during the past one year, 22.1% performed no dental visit during the past one year, and 8.3% never visited the dentist. Among children who visited the dentist, the pain was the most common reason for dental visits (39.10%, N=170), followed by routine dental check-ups (18.60%, N=81). In bivariate analysis, education of parents, family income, daily tooth brushing, no decay in the first permanent molar, no toothache, no consumption of soft drinks, biscuits, cakes, and cream were significantly associated with routine dental attendance (P < 0.05). However, the final logistic regression model showed that university education of mothers (OR 2.52, P = 0.005), not having toothache or discomfort (OR 2.88, P = 0.001), tooth brushing once or twice daily (OR 2.43, P= 0.034), and not consuming soft drinks (OR 1.96, P= 0.027) were significant predictors of routine dental visits.Conclusion: The study found that higher education of mothers, daily tooth brushing, not having dental pain, and not consuming soft drinks were significantly associated with routine dental visits in this sample of female schoolchildren. Routine dental attendance may be used to improve oral hygiene and reduce dental pain and consumption of soft drinks in children.Keywords: dental attendance, access to oral care, soft drinks, toothache